2005
DOI: 10.1196/annals.1313.028
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Anti‐F‐Actin Antibodies in a French Multicenter Study

Abstract: According to international criteria, autoimmune hepatitis (AIH) type 1 is characterized by the presence of antinuclear or anti-smooth muscle antibodies (SMA) with F-actin specificity. SMA have been found in 85% of AIH patients, but are not specific to this disease, and anti-F-actin specificity is not always verified when SMA are detected. The objective of this study was to determine the diagnostic value of anti-F-actin antibodies in a large population. A multicenter study involving 12 clinical centers was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 23 publications
1
15
1
2
Order By: Relevance
“…Antibodies to F-actin can also be found in patients with viral hepatitis, but usually they are present in lower levels than those seen in AIH-1 (14,15). The present study is in agreement with these observations, as we found 25% of patient sera having serologies consistent with viral hepatitis were positive for F-actin IgG with the majority (59.3%) of these sera having low levels (Table 3).…”
Section: Discussionsupporting
confidence: 95%
“…Antibodies to F-actin can also be found in patients with viral hepatitis, but usually they are present in lower levels than those seen in AIH-1 (14,15). The present study is in agreement with these observations, as we found 25% of patient sera having serologies consistent with viral hepatitis were positive for F-actin IgG with the majority (59.3%) of these sera having low levels (Table 3).…”
Section: Discussionsupporting
confidence: 95%
“…Although the presence of anti-actin antibodies in patients with chronic hepatitis C infection was previously described (11)(12)(13)(14), the prevalence of either ASMA or anti-actin positivity was particularly high in our study. Out of the 33 HCV samples, 19 (57%) were ASMA positive, 7 (21%) were anti-actin positive and 6 (18%) of them both ASMA and anti-actin positive.…”
Section: Discussioncontrasting
confidence: 72%
“…Antibodies to actin can be demonstrated by indirect immunofluorescence of microfilaments in HEp-2 cells or fibroblasts treated with vinblastine or colchicine [65,66]. They can also be detected by indirect immunofluorescence of liver sections from rats chronically injected with phalloidin [65] or by assessing peritubular and glomerular structures in rat kidney [67].…”
Section: Antibodies To Actinmentioning
confidence: 97%